Synthesis and Biological Activities of 3-1-(3-(2-Chloro-3,3,3-trifluoro-prop-1-enyl-2,2-dimethylcyclopropanecarbonyl)-3-Substituted Phenyl Thiourea - Sun, Na-Bo; Jin, Jian-Zhong; Xu, Hui-Ying; Ke, Wei (Asian Journal of Chemistry, 2013)
Some thiourea compounds containing pyrethroids are synthesized. Their structures were confirmed by 1H NMR, MS and elemental analysis. The bioassay results indicated that they showed moderate insecticidal and fungicidal activity.